2013
DOI: 10.1007/s11136-013-0587-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and related factors: a questionnaire survey of older people living alone in Mainland China

Abstract: This study identified nine factors influencing the QoL of older people living alone in Mainland China. Interventions to increase satisfaction with dwelling conditions, improve economic level, social support and functional ability, decrease loneliness and depression and improve health services satisfaction appear to be important for enhancing their QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 31 publications
6
48
3
4
Order By: Relevance
“…Thereafter, they can measure and understand the Chinese’s QOL and even compare it with that of people from other countries. QOL research mainly focuses on children and the aging population [49, 50]. Significant attention has also been focused on QOL of patients with cancer, schizophrenia and depression [51, 52].…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, they can measure and understand the Chinese’s QOL and even compare it with that of people from other countries. QOL research mainly focuses on children and the aging population [49, 50]. Significant attention has also been focused on QOL of patients with cancer, schizophrenia and depression [51, 52].…”
Section: Resultsmentioning
confidence: 99%
“…Still, urbanisation is the keystone in the development plan drawn by the government for the future. In the study of Chen, Hicks, and While (), professional occupation before retirement signified a higher quality of life among older people in China due to higher socioeconomic status and social resources, such as pensions (Zhou & Wang, ). It is inferable that the systemic development imbalance has a profound effect on the individual life of each person involved, including their ways of dealing with major life events (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Personal factors found to be associated with health in older adults are age [12,13], gender [12,13,14,15,16], race/ethnicity [12,13], education attainment [13,17,18,19]; and employment [12]. Research conducted in Europe, Asia, Africa, and Latin America with aging populations found several economic and social factors associated with broad health and independence outcomes, including: reduced retirement pensions [20]; community involvement and social support [21,22,23]; housing conditions [22,24,25]; income level [17,22,26,27,28]; forced retirement [29]; and feeling discriminated [24]. …”
Section: Introductionmentioning
confidence: 99%